Exergetic Assessment of Waste Gas to Energy in a Novel Integrated NGL Recovery and Power Generation Plant - Aigba, Peter Alenoghena; Emovon, Ikuobase; Samuel, Olusegun David; Chintua Enweremadu, Christopher; Abdeljawad, Thabet; Al-Mdallal, Qasem M.; Afzal, Asif (Frontiers in Energy Research, 2022)
Natural gas processing, as one of the major energy sources, has become a focal point in boosting the energy value chain by processing high commercial value products such as natural gas liquids (NGL) and electricity generation. Natural gas processing has also amplified its usefulness to human well-being and global prosperity in different ways. However, the spate of gas flaring is a global phenomenon, despite advances in waste gas management technology. This research describes a unique integrated plant that recovers NGL and produces electricity via waste gas for the energy conversion process. Exergetic analysis has been offered to identify the causes of irreversibilities in the plant. Simulation models were built using the AspenOne HYSYS V10 and Aspen Plus V10 software to conceptualize the plant. The recovery of 60 kBD NGL and 2.55 kg mol/s of 97% lean methane gas (95% purity) as the residue was achieved from 320 MMSCFD of waste gas processing. The residue methane gas is combusted in a combustion chamber to recover hot gas in a heat recovery steam generator (HRSG) for steam generation and production of 646 MW of electricity. Analysis revealed that the heat exchangers collectively accounted for about 78% exergy destruction in the NGL recovery plant, while the 3 and 1.54%, respectively, of exergy is destroyed and lost in the demethanizer. The steam power plant showed similar irreversibilities with the boiler exchanger accounting for up to 88% exergy destruction. About 1.4% of exergy is lost as flue gas to the environment. At optimization, overall exergy efficiency reached 77.5 and 80.6% in the NGL recovery and steam power plant, respectively. Thus, this integrated plant model has not only demonstrated a marked improvement to similar models but is also a lucrative alternative to waste flare gas management. It is also proven to be a “flare-capture” alternative model for fossil fuels-related emission reduction and optimization tool for waste gas to energy.